Fabrication and characterization of porous bioceramic composites based on hydroxyapatite and titania - Boccaccini, Aldo R.; et al. (Materials Chemistry and Physics, 2007)
Porous bioinert-bioactive composite ceramics were fabricated from hydroxyapatite and titania powder mixtures by using several techniques including involving the use of porogens such as carbon fibers, polyurethane (PU) foams or H2O2. The optimal titania content in the composite was 15 wt.%. Using H2O2 as pore creator, a porosity of 65 ± 4% was achieved. The pores were shown to be interconnected with dimensions in the range 100-1000 μm. Young's modulus, bending strength and compressive strength of the porous composite were: 1.7 ± 0.2 GPa, 2.1 ± 0.3 MPa and 7 ± 1 MPa, respectively. This porous material can find applications as scaffold in bone tissue regeneration strategies. © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.fabric_2
Keywords: Bioceramics; Ceramic composites; Hydroxyapatite; Porosity; Sintering; Titania